HUBUNGAN KETAHANAN KELUARGA DAN PENGGUNAAN MEDIA SOSIAL DENGAN PERILAKU BULLYING PADA KALANGAN REMAJA DI SMP ISLAM YAPKUM DEPOK - Ahmad Nursalam (2022)
The phenomenon of bullying continues to grow over time. Bullying defined as a particular type of situation that is exploitative, intentional, and repetitive. This relates to the power imbalance between the bully and the victim.This study aims to determine the relationship between family resilience and the use of social media with bullying behavior among adolescents at Yapkum Islamic Junior High School Depok. The study used the Chi Square test with a cross sectional approach, the sample was 169 adolescents and the sample was taken using simple random sampling technique. The results of the study found that there was a positive relationship between family resilience and bullying behavior among teenagers at the Yapkum Islamic Junior High School Depok, which obtained a p value of 0.025 with OR = 2.684, this means resilience tall families have a 2,684 times chance to positively carry out bullying behavior.While there is a positive relationship between the use of social media and bullying behavior in adolescents, p value = 0.021 with OR = 3.642, this means that active social media users have 3.642 times the opportunity to positively engage in bullying behavior. Researchers suggest that teenagers know the impact of bullying behavior so that good communication with families related to bullying is needed, and be careful in the use of social media. Use social media for positive content Research suggests that teenagers should know the impact of bullying so that good communication with families is needed regarding bullying, and be careful in using social media. Use social media for positive content.